Representasi Sosial dan Otonomi Perempuan Buruh Garam (Telaah terhadap Konsep Qiwamah) - Tatik Hidayati (Institut Ilmu Keislaman Annuqayah, 2019)
The research aims to make a dialog between text or Qiwamah concept and social reality of a particular social group, a community of women salt workers. The concept of Qiwamah here, referring to several interpretations of the concept, was defined as the men's or husbands' leadership in households. The concept was used to analyze the activity of women salt workers in terms of social representation and autonomy, including in the domestic space (family) and public space (society and working place). The autonomy of women salt workers was picked to fundamentally understand women's independence in the decision-making process related to personal matters, family, community, and profession (long-nolongi, lelabet, kompolan, njangan and nyaput enek). The research found that the concept of Qiwamah in Madurese, especially in the family of women salt workers, was not run strictly and rigorously, but more as reverence to men. Often, women significantly took responsibility and figured in decision-making processes. This research is essential to see that the concept of Qiwamah can be understood and realized contextually and adjusted to cultural conditions. It suggests that there is no a basic guidance that family leadership held by men should be realized as the final form.